Answer:
j = (h-4) / k
Step-by-step explanation:
Unless there is more information given about this question somewhere else in the assignment, I'm assuming you are being asked to solve this equation for j.
If so, then its just a matter of rearranging the equation so that it is in the form
j = (expression containing other variables)
(h-4) / j = k (multiply both sides by j)
(h-4) = jk (divide both sides by k)
j = (h-4) / k
Answer:0.05168986083
Step-by-step explanation:
Answer:
a. 7
b. 0
c. 4
d. 15
Step-by-step explanation:
the negative numbers in the absolute value get changed to positive.
Answer:
no idea what the answer is
ㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤㅤ